Medical and Periodontal Clinical Parameters in Patients at Different Levels of Chronic Renal Failure - Caroline Perozini; Gilson Fernandes Ruivo; Lucilene Hernandes Ricardo; Larissa Avance Pavesi; Yeon Jung Kim; Debora Pallos (International Journal of Dentistry)
Aim. To assess the clinical periodontal and medical parameters in patients with chronic renal failure (CRF) at different levels of renal disease. Background. CRF is a progressive and irreversible loss of renal function associated with a decline in the glomerular filtration rate. Periodontal disease is a destructive inflammatory disease affecting periodontal tissues that shows high prevalence in patients with CRF. Materials and Methods. 102 CRF patients were included and divided into an early stage group (EG), predialysis group (PDG), and hemodialysis group (HDG). The medical parameters were taken from the patients’ records. Results. Periodontal clinical condition differed among the CRF groups. Clinical attachment loss was greater in the HDG and PDG group compared to the EG (p=0.0364); the same was observed in the Plaque Index (p=0.0296); the others periodontal parameters did not show any differences. Ferritin levels were significantly higher in the HDG when compared to the EG and PGD (p<0.0001), and fibrinogen was higher in PDG compared with the others (p<0.0001); the triglycerides also showed higher values in the HDG compared with the other groups (p<0.0001). Conclusion. The patients with renal involvement should have a multidisciplinary approach to an improvement in their oral and systemic health.